Optimalisasi Biaya dan Efesiensi Operasional Meningkatkan Daya Saing dan Profitabilitas Usaha - vinka zahra (Abdimisi, 2025)
This community service activity aims to improve the understanding and skills of vocational high school students in utilizing technology and the internet for entrepreneurship in the digital era. The target of the activity is 39 10th grade Accounting students of SMK Iptek Tangerang Selatan. The activity was carried out on Friday, May 9, 2025, with workshop and training methods. The materials presented include financial literacy, sustainable financial concepts, and sociopreneurs. The resource persons for the activity were Nurul Alfida Rahmawati and Rafina Arinitaz. Participants actively participated in the activity with an attendance rate of 90%. The results of the activity were in the form of creative content such as promotional videos and vlogs, as well as digital business ideas that were expressed in group assignments. Students were also introduced to the use of the marketplace as a marketing medium. The success of the activity was supported by careful planning and effective coordination with collaboration partners. This activity is expected to encourage the birth of young entrepreneurs from among students.  Keywords: Sociopreneur, Financial Literacy, Sustainable Finance, Industrial Revolution 4.0